Machine Learning Approaches for Detecting Abnormalities in Female Fetuses - Cai, Yuxuan (International Scientific Technical and Economic Research, 2025)
Non-invasive prenatal testing (NIPT) plays a vital role in the early detection of female fetal abnormalities, which is essential for birth defect prevention. In this study, clinical data containing Z-scores of chromosomes 21, 18, and 13, GC content, X chromosome concentration, read count ratio, and maternal BMI were analyzed. To address the class imbalance caused by the limited number of abnormal cases, the Synthetic Minority Over-sampling Technique (SMOTE) was applied, and stratified sampling was used to divide the dataset into training, validation, and testing sets (7:2:1). Multiple machine learning models, including XGBoost, Decision Tree, CNN, MLP, SVM, and Random Forest, were developed and evaluated with accuracy, precision, recall, F1-score, and AUC-ROC metrics. Results demonstrated that Random Forest outperformed other models, achieving an AUC of 0.997 with strong stability and generalization. These findings highlight the effectiveness of machine learning combined with proper data preprocessing in enhancing female fetal abnormality detection.